Multidimensional Budgeting Concepts and Budget Control Modeling For Production Systems Performance Efficiency - Dr. Nwosu Moses. C.; Dr. Aguh Patrick. S.; Ezeanyim, Okechukwu C. (International Journal of Engineering and Management Research, 2020)
The growing complexity of the society and high level of competition in the business world has imperatively made business organizations to do serious planning, accounting, implementation, and control of budget in order to survive the present day volatile business climate very efficiently. There is always the saying that “one who fails to plan, plans to fail”. Therefore, this study of budgeting and budget accounting serves as a tool for planning, execution, measuring efficiency and performance in manufacturing industries. It focuses on budget preparation, implementation and control on operations and activities in production engineering organizations. The objective of this study was to x-ray the relevance of budgeting as a tool for planning and controlling in manufacturing industry and also to ascertain the concepts associated with the efficient analytical processes of budgeting plans to the performance of business organizations. It is necessary that management of every organization should prepare budget and adhere strictly to the provisions of the budget with a regular and periodic review of the budget in order to detect variations. This work will serve as a template to managers, entrepreneurs, creditors, and employees on how to effectively allocate and manage scarce resources judiciously through budgetary planning, accounting, implementation and control to the measurements of performance and efficiency of operations.